Kurzmitteilung (2007) de Navid Kermani : l’écriture du deuil - Emmanuelle Terrones (Recherches Germaniques)
Navid Kermani’s novel Kurzmitteilung (2007) shows a man who can’t help being in mourning after the death of a young woman he hardly knew. This paper begins with the legitimacy of mourning, a question that appears at the outset of the novel and determines his inner rhythm from the beginning to the end. There is to analyze the effects of the mourning imposed upon the protagonist like a moral imperative or a responsibility: the strangeness his words and actions take on, the confusion that spreads to him. The monologue he writes is evidence of the silent isolation to which the notice of the death condemned him, as well as the progressive and ineluctable loss of his own identity: the writing of mourning becomes mourning for himself. All of this leaves us to understand that the obsessive idea of death obliges him to live and think according to other coordinates which he tries to define by his writing process. It amounts to rethinking everything from death.